Perceived Vulnerability and Severity Predict Adherence to COVID-19 Protection Measures: The Mediating Role of Instrumental Coping - González-Castro, José Luis; Ubillos-Landa, Silvia; Puente-Martínez, Alicia; Gracia-Leiva, Marcela (Frontiers in Psychology, 2021)
The COVID-19 disease has caused thousands of deaths worldwide and required the rapid and drastic adoption of various protective measures as main resources in the fight to reduce the spread of the disease. In the present study we aimed to identify socio cognitive factors that may influence adherence to protective measures towards COVID-19 in a Spanish sample. This longitudinal study analyzes the predictive value of perceived severity and vulnerability of infection, self-efficacy, direct exposure to the virus, and instrumental focused coping style for adhering to infection protection behaviors during the first months of the COVID-19 pandemic. It also tests sex and age differences in these factors and changes over time. A two-wave longitudinal study (N = 757) was conducted in march and april 2020 starting the day after a strict national lockdown was decreed in Spain. A path analysis was used to test direct and indirect effects between vulnerability and the adherence to protective behaviors. Results suggest that individuals’ perceived severity and vulnerability to COVID-19 and instrumental coping strategies are related to the use of more protective behaviors. This coping strategy mediates the effect of perceived vulnerability on engaging in protective behaviors, and this effect depends on direct exposure to COVID-19 and perceived self-efficacy moderators. Results suggest that recognizing one's own abilities to engage in instrumental actions may facilitate adherence to protective measures in people who had not been directly exposed to COVID-19. Therefore, adopting instrumental coping strategies to manage an individual’s perceived vulnerability to infection may positively impact the adherence to protective behaviors, especially during the onset of an unexpected threat and when there is no prior direct experience with the situation.